1997
DOI: 10.1002/jlb.61.4.459
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-parasite relationship in theileriosis. Reversible phenotypic and functional dedifferentiation of macrophages infected with Theileria annulata

Abstract: Abstract:Theileria annulata is a tick-transmilled pro-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 31 publications
3
56
0
1
Order By: Relevance
“…This cell transformation is closely related to the presence of the parasite within the host cell cytoplasm, as cells in which the parasite fails to establish itself during mitosis undergo apoptosis. Moreover, elimination of the parasites by the theilericidal drug buparvaquone leads to the cessation of proliferation and the dedifferentiation of the host cells to a resting phenotype (McHardy 1984, Sager et al 1997.…”
Section: Discussionmentioning
confidence: 99%
“…This cell transformation is closely related to the presence of the parasite within the host cell cytoplasm, as cells in which the parasite fails to establish itself during mitosis undergo apoptosis. Moreover, elimination of the parasites by the theilericidal drug buparvaquone leads to the cessation of proliferation and the dedifferentiation of the host cells to a resting phenotype (McHardy 1984, Sager et al 1997.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for this is that ferret studies are hampered by a severe lack of immunological reagents. The ferret is a mustelid, and previous studies have identified cross-reactive monoclonal antibodies (mAbs) that bind mustelid proteins in mink (Aasted 1989, Danilenko et al, 1992, Jacobsen et al, 1993, Chen et al, 1997, Sager et al, 1997, Brodersen et al, 1998, Pedersen et al, 2002, Jensen et al, 2003, Saalmuller et al, 2005. These antibodies were originally generated against human, canine, ovine, and bovine cells.…”
Section: Introductionmentioning
confidence: 99%
“…To establish and survive, intracellular parasites modulate the host cell environment (42). Evidence that this process involves interfering with the molecular pathways that determine the phenotypes of mammalian cells is accumulating, and apicomplexan parasites have been shown to alter the control of cellular differentiation (29), proliferation (12), and apoptosis (21).…”
mentioning
confidence: 99%
“…A primary factor in the pathology of these diseases is the generation of neoplasia by rapidly dividing transformed infected leukocytes (6). Host cell division and dedifferentiation are induced by the intracellular multinucleated macroschizont stage (18,29) and are accompanied by alterations to bovine gene expression (30). These events are dependent on a viable macroschizont, as they can be reversed by the treatment of cells with the theileriacidal drug buparvaquone (22).…”
mentioning
confidence: 99%